2010
DOI: 10.1111/j.1365-2133.2010.09649.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of the human AR/EDA2R locus in androgenetic alopecia

Abstract: MMP, which shows IgG and IgA antibodies to the carboxylterminus of BP180. 4 A further 10-20% of cases of MMP are antilaminin 332 MMP, which shows IgG antibodies to laminin 332 (previously called epiligrin or laminin 5). 5,6 Ocular MMP shows exclusive ocular mucosal lesions, although the autoantigen for this group has not been clearly identified.Although ocular lesions are commonly seen in MMP, they are usually hyperaemia or erosions which result in symblepharon or epithelialization over the cornea. A clear bli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 10 publications
2
36
0
2
Order By: Relevance
“…A number of polymorphisms across the 540KB region and in the nearby androgen receptor (AR) gene have been associated with androgen alopecia (AGA), also called male pattern baldness [Hillmer et al 2005;Hillmer et al 2008a;Hillmer et al 2008b;Hillmer et al 2009;Brockschmidt et al 2010]. The variant with the most significant AGA association (~10 -25 ), rs12558842, is one of the 52 haplotype-defining SNPs [Brockschmidt et al 2010].…”
Section: Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of polymorphisms across the 540KB region and in the nearby androgen receptor (AR) gene have been associated with androgen alopecia (AGA), also called male pattern baldness [Hillmer et al 2005;Hillmer et al 2008a;Hillmer et al 2008b;Hillmer et al 2009;Brockschmidt et al 2010]. The variant with the most significant AGA association (~10 -25 ), rs12558842, is one of the 52 haplotype-defining SNPs [Brockschmidt et al 2010].…”
Section: Selectionmentioning
confidence: 99%
“…The variant with the most significant AGA association (~10 -25 ), rs12558842, is one of the 52 haplotype-defining SNPs [Brockschmidt et al 2010]. When…”
Section: Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the exact pathogenesis for AGA is not entirely clear, there is a strong genetic component for this condition, and so far, a total of 12 susceptibility loci have been revealed [55][56][57][58]. As implied by the name of this condition, several loci have indeed been found to be associated with androgen-dependent pathways [56,59]. Recently, a new study has reported, for the first time, on AGA risk loci, which include genes that are connected to the WNT signaling pathway [58].…”
Section: Polygenic Hair Disordersmentioning
confidence: 96%
“…Die Autoren postulierten, dass der Assoziationsbefund im AR-Gen durch Kopplungsungleichgewicht mit Arg57Lys zu erklären sei. Diesen Befund konnte die in Deutschland durchgeführte, bislang umfangreichste Assoziationsanalyse (Betroffene n=673, Nichtbetroffene n=248) nicht bestätigen[8]. Die stärkste Assoziation wurde mit der zwischen AR und EDA2R gelegenen Variante rs12558842 gefunden (.…”
unclassified